Evaluasi Pelayanan Publik pada PT. PLN (PERSERO) Distribusi Bali UP3 Bali Selatan ULP Kuta (Studi Kasus Area Pelayanan ULP Kuta) - Sani, Firman; Sastra Wijaya, Komang Adi; Yasintha, Putu Nomy (CITIZEN CHARTER, 2020)
zABSTRACT Providing electricity power in Indonesia according UU 30 Tahun 2009 Concerning Electricity is run by the BUMN specifically PT. PLN due to the strategic value of electricity power to the Nation and the State. PT. PLN as the BUMN is the sole holder of the right to sell electricity power. This study aims to find out about how the public services carried out by PT. PLN (PERSERO) Distribution of Bali UP3 South Bali The unit of analysis of this research is evaluation and service’s quality, namely the PT. PLN ULP Kuta. this study described the evaluation criteria proposed by Dunn in Agustino (2008:187) effectiveness, efficiency, adequacy, responsifeness. and services quality proposed by Levinne (1990) responsiveness, responsibility, accountability. The Informants is determined by purposive sampling.The results of this study indicate public services conducted by PT. PLN ULP Kuta still experiencing problems and disruption. Thus render its service less than optimal. Keywords:Services, Disruption, Recovery Time, Response time